Development of a binational thyroid cancer clinical quality registry: a protocol paper. Issue 1 (28th January 2019) - Ioannou, Liane J; Serpell, Jonathan; Dean, Joanne; Bendinelli, Cino; Gough, Jenny; Lisewski, Dean; Miller, Julie A; Meyer-Rochow, Win; Sidhu, Stan; Topliss, Duncan; Walters, David; Zalcberg, John; et al.
Abstract : Introduction: The occurrence of thyroid cancer is increasing throughout the developed world and since the 1990s has become the fastest increasing malignancy. In 2014, a total of 2693 Australians and 302 New Zealanders were diagnosed with thyroid cancer, with this number projected to rise to 3650 in 2018. The purpose of this protocol is to establish a binational population-based clinical quality registry with the aim of monitoring and improving the quality of care provided to patients diagnosed with thyroid cancer in Australia and New Zealand. Methods and analysis: The Australian and New Zealand Thyroid Cancer Registry (ANZTCR) aims to capture clinical data for all patients over the age of 16 years with thyroid cancer, confirmed by histopathology report, who have been diagnosed, assessed or treated at a contributing hospital. A multidisciplinary steering committee was formed which, with operational support from Monash University, established the ANZTCR in early 2017. The pilot phase of the registry is currently operating in Victoria, New South Wales, Queensland, Western Australia and South Australia, with over 20 sites expected to come on board across Australia in 2018. A modified Delphi process was undertaken to determine the clinical quality indicators to be reported by the registry, and a minimum data set was developed comprising information regarding thyroid cancer diagnosis, pathology, surgery and 90-day follow-up. Future plans: The establishment of the ANZTCR provides the opportunity for Australia and New Zealand to further understand current practice in the treatment of thyroid cancer and identify variation in outcomes. The engagement of endocrine surgeons in supporting this initiative is crucial. While the pilot registry has a focus on early clinical outcomes, it is anticipated that future collection of longer term outcome data particularly for patients with poor prognostic disease will add significant further value to the registry.